Georgia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2003)
The econometric results show that it is feasible to estimate robust price and inflation equations for Georgia. The long-term price equation expresses prices as a function of money, the exchange rate, and real income and may be interpreted as portraying equilibrium in the goods market. The paper also represents statistical data of transportation indicators, population and employment, personal income tax, monetary survey, average monthly wages, developments in commercial banking, interest rates, prudential indicators of commercial banks, balance of payments, and so on.